IMPACTS OF RUBBER PLANTATION ON DIVERSITY OF UNDERSTORY VEGETATION AND SOIL ANIMALS IN BAO LAM RUBBER ENTERPRISE, BAO LAM DISTRICT, LAM DONG PROVINCE - Xuan Truong, Le; Gia Bao, Ngo (Journal of Forestry Science and Technology, 2017)
This study was conducted in Bao Lam rubber enterprise, Bao Lam district, Lam Dong province and concentrated in impacts of rubber plantation on diversity of understory vegetation and soil animals. Based on data collected from the rubber tree plantations, number of species and number of individuals of understory vegetation, and soil animals in five plots of rubber trees, five plots of adjacent vegetation, the characteristics of distribution were figured out and diversity indices of understory vegetation and soil animal were determined. With understory vegetation, there are 56 species of 35 vegetation families in study site, mainly belonging to Araceae, Asteraceae, Euphobiaceae, Moraceae, Myrsinaceae, Rubiaceae and Poaceae. Species composition of understory vegetation in rubber plantation is different from the adjacent vegetation. All diversity indices in rubber plantation are lower than that of adjacent vegetation. With soil animals, there are 15 species of 10 families in study site, mainly belonging to Megasoclecidae, Glossoscolecidae, Fomicidae, Termitoidae, and Noctuidae. Species composition of soil animals in rubber plantation is similar with adjacent vegetation. Diversity indices of soil animals between rubber plantation and adjacent vegetation are not significantly differentas well.